Checklist of the earthworms (Oligochaeta) of Kerala, a constituent of Western Ghats biodiversity hotspot, India - Narayanan, S. Prasanth; Sathrumithra, S.; Christopher, G.; Thomas, A.p.; Julka, J.m. (Zootaxa, 2016)
A checklist of earthworm species hitherto known from Kerala, a constituent of the Western Ghats biodiversity hotspot in India, is presented. In total, 88 species and subspecies are recorded, of which 55 are Kerala endemics, 9 near endemics, 14 exotics and 10 native peregrines. These belong to 26 genera and 9 families. The checklist includes the literature citation to the original description, type locality, any significant subsequent generic placements, and the district distributional pattern for each species/ subspecies.